An Up-to-Date Overview of the Complexity of Genotype-Phenotype Relationships in Myotonic Channelopathies - Morales, Fernando; Pusch, Michael (Frontiers in Neurology, 2020)
Myotonic disorders are inherited neuromuscular diseases divided into dystrophic myotonias and non-dystrophic myotonias (NDM). The latter is a group of dominant or recessive diseases caused by mutations in genes encoding ion channels that participate in the generation and control of the skeletal muscle action potential. Their altered function causes hyperexcitability of the muscle membrane, thereby triggering myotonia, the main sign in NDM. Mutations in the genes encoding voltage-gated Cl- and Na+ channels (respectively CLCN1 and SCN4A) produce a wide spectrum of phenotypes, which differ in age of onset, affected muscles, severity of myotonia, degree of hypertrophy and muscle weakness, disease progression, among others. More than 200 CLCN1 and 65 SCN4A mutations have been identified and described, but just about half of them have been functionally characterized, an approach that is likely extremely helpful to contribute to improving the so-far rather poor clinical correlations present in NDM. The observed poor correlations may be due to: 1- the wide spectrum of symptoms and overlapping phenotypes present in both groups (Cl- and Na+ myotonic channelopathies) and 2- both genes present high genotypic variability. On the one hand, several mutations cause a unique and reproducible phenotype in most patients. On the other hand, some mutations can have different inheritance pattern and clinical phenotypes in different families. Conversely, different mutations can be translated into very similar phenotypes. For these reasons, the genotype-phenotype relationships in myotonic channelopathies are considered complex. Although the molecular bases for the clinical variability present in myotonic channelopathies remain obscure, several hypotheses have been put forward to explain the variability, which include: a- differential allelic expression; b- trans-acting genetic modifiers; c- epigenetic, hormonal or environmental factors and d- dominance with low penetrance. Improvements in clinical tests, the recognition of the different phenotypes that result from particular mutations and the understanding of how a mutation affects the structure and function of the ion channel, together with genetic screening, is expected to improve clinical correlation in NDMs.